Factors influencing the adoption of business analytics in Zimbabwe - Charles Tichavavamwe; Riani Rachmawati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2024)
The advent of the Industrial 4.0 economy has intensified the usage of Business Analytics (BA) as a strategic business tool, but the adoption rate is not equally spread across nations. This study investigated the factors influencing the intention to adopt BA in Zimbabwean companies using the technology organization environment (TOE) and the technology acceptance model (TAM). A quantitative approach was used, and data were collected from 157 Zimbabwean companies from various sectors that have adopted or intend to adopt BA. A questionnaire was deployed for data collection, and a convenient sampling method was used. The results revealed that perceived relative advantage, top management support, competitive pressure, and government regulations significantly influence the intention to adopt BA. However, complexity, compatibility, IT infrastructure, and organizational readiness were not supported. The results corroborate and support previous findings. This study adds value to the knowledge of BA adoption from a developing economy perspective. The fusion of TOE and TAM models on Zimbabwean companies' intention to adopt BA was explored for the first time. The flexibility of the TOE model allows the use of IT Infrastructure, which was perceived to have a significant influence in the Zimbabwean context, though it was proved insignificant. Managers in Zimbabwe can benefit from BA adoption for strategic value creation, with policymakers encouraged to promote BA adoption, and scholars will learn about the fused TOE-TAM model.